MAPPING THE RISK RESPONSE STRATEGIES ON CLASSIFIED BUILDING CONSTRUCTION-RELATED RISKS (FUDMA JOURNAL OF SCIENCES, 2023)
Research works in construction tend to focus on identifying and analyzing risk factors associated with construction projects. The researcher has identified several risk factors associated with building construction projects that are mainly attributed to the contractor. Risk response strategies also developed to include: Avoid, Retain, Reduce and Transfer. However, no research suggests which category of risk to avoid, retain, reduce or transfer. This research aims to map out the risk response strategies for varying risk factors in Building Construction Projects. It can be achievable by identifying the risk factors and response strategies from theliterature, assessing each stakeholder’s level of importance attached to each risk factor, identifying the most relevant risk factors, and mapping out the risk response strategies to varying risk factors. The study adopted a questionnaire where 68 valid questionnaires were analyzed using frequencies, means and percentages. The result shows that there are 54 risk factors associated with building construction projects, out of which 36 are of high significance. There is a significantly positive relationship between the probability of occurrence and the level of impact of the risk factor i.e. higher probability of occurrence is associated with a higher level of impact. The mapping of risk response strategies on risk factors shows that 37% of the risk factors are to be managed by reducing, 28% by avoiding,20% by retaining and 19% by transferring. Thus, the best risk response strategies are ‘reduce’ and ‘avoid’. Finally, the study recommends that all stakeholders understand and implement these risk response strategies accordingly.
Keywords: Risk, risk factors, risk response strategies, mapping, building construction